Distal Hand Migration of Polyacrylamide Gel after Breast Augmentation: A Case Report and Review of the Literature - Gierej, Piotr; Radziszewski, Marcin; Miłoński, Piotr; Noszczyk, Bartłomiej (Indian Journal of Plastic Surgery, 2022)
Breast augmentation is one of the most popular cosmetic surgery procedures in the world and it requires a comprehensive study of the methods performed. As less-invasive techniques are sought, tissue fillers have found its purpose in these procedures. However, it has been revealed that some of them may be associated with serious complications. One of them is the Aquafilling/Los Deline gel. A case report of a female patient who developed unprecedented sequelae after Aquafilling injection—distant migration of the gel in the hand—was presented in this study. The patient underwent total gel removal from the left forearm, arm, and both breasts as well as wound debridement and irrigation. We discovered a canal connecting the left breast to the left forearm, created by a polyacrylamide hydrogel dislocation. It was thoroughly revised using an endoscope. Despite the advantages of tissue fillers such as simplicity of use and less invasiveness, certain complications can occur after injection. Although a few of them have been banned due to these sequelae, new ones continue to appear. Every new product should be examined very carefully before it is introduced to the market.
Keywords: breast augmentation; complications; aquafilling